2022
DOI: 10.21883/tpl.2022.07.54035.19230
|View full text |Cite
|
Sign up to set email alerts
|

Properties of coatings obtained from a mechanically treated boron-containing mixture of powders by cold spray method

Abstract: For composite coatings obtained by cold spraying from powder mixtures of compositions Al + 50 wt.% B and Al + 50 wt.% B4C prepared in a V-shaped mixer and by mechanical processing in a planetary mill, a comparison of effect of these methods for preparing mixtures on the boron (boron carbide) content in the coating was carried out. It is shown that, regardless of the method of preparation, the boron and/or boron carbide contents in the coating have close values, which is confirmed by the results of X-ray phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…53 All these minerals are rare, with the exception of kermesite, which is described in notable quantities in many localities. The second group of "modular" minerals includes minerals of the valleriite group [valleriite, (Fe 2+ ,Cu) 4 (Mg,Al) 3 S 4 (OH,O) 6 , 54 tochilinite, Fe 2+ 5−6 (Mg,Fe 2+ ) 5 S 6 (OH) 10 , 55 haapalaite, (Fe 2+ ,Ni) 2 (Mg,Fe 2+ ) 1.61 S 2 (OH) 3.22 , 56 yushkinite, (Mg,Al)-V 4+ S 2 (OH) 2 , 57,58 as well as vyalsovite, FeCaAlS(OH) 5 , 59,60 and bazhenovite, Ca 8 S 2 (S 3 )( 61 (the study by Bindi et al 62 demonstrated that bazhenovite does not contain thiosulfate groups, and therefore, its crystalchemical formula should be corrected). It should be noted that bazhenovite was discovered, described, and approved as a valid mineral species from the burned dumps of the ChCB.…”
Section: ■ Introductionmentioning
confidence: 99%
“…53 All these minerals are rare, with the exception of kermesite, which is described in notable quantities in many localities. The second group of "modular" minerals includes minerals of the valleriite group [valleriite, (Fe 2+ ,Cu) 4 (Mg,Al) 3 S 4 (OH,O) 6 , 54 tochilinite, Fe 2+ 5−6 (Mg,Fe 2+ ) 5 S 6 (OH) 10 , 55 haapalaite, (Fe 2+ ,Ni) 2 (Mg,Fe 2+ ) 1.61 S 2 (OH) 3.22 , 56 yushkinite, (Mg,Al)-V 4+ S 2 (OH) 2 , 57,58 as well as vyalsovite, FeCaAlS(OH) 5 , 59,60 and bazhenovite, Ca 8 S 2 (S 3 )( 61 (the study by Bindi et al 62 demonstrated that bazhenovite does not contain thiosulfate groups, and therefore, its crystalchemical formula should be corrected). It should be noted that bazhenovite was discovered, described, and approved as a valid mineral species from the burned dumps of the ChCB.…”
Section: ■ Introductionmentioning
confidence: 99%